Habitat III: civil society’s participation in the building of the New Urban Agenda and the right to the city - Dávalos González, Javier (2018)
This article analyzes the process of creation of the New Urban Agenda and propo ses a relative discussion regarding its subsequent implementation and the realization of the urban legislation. These processes may be understood from the citizens’ joint responsibility trough transformational initiatives of local participation. The presented hypothesis is that for these processes to be effectively implemented, they have to be built trough concrete actions from local social movements and organizations, and not only as a gift from the State or local governments, nor an imposition from global instances for development.